Non-neoplastic disorders in an aging gut: concise review - Saurabh Dawra; Pradeep Behl; Sharad Srivastava; Manish Manrai; Alok Chandra; Anupam Kumar; Ankit Kumar; Manveer Singh Tevatia (SpringerOpen, 2023)
Abstract The spectrum of gastrointestinal (GI) issues in the older population varies from common physiological age-related changes to devastating, less common sinister pathological illness. GI system has direct exposure to external environment. Thus, it is modeled to embrace the pathophysiological changes that occur due to interaction with external factors. Gastrointestinal tract (GIT) per se is more resilient to aging as compared to other organ systems. On the other hand, elderly may present with a large plethora of GI symptoms. This presents a challenge to all echelons of medical consultation for accurate attribution for the aging process or pathophysiological causation of GI symptoms. This dichotomy leads to hindrance in adequate and appropriate treatment of GI ailments. In GI system, non-neoplastic disorders are far more common than neoplastic disorders. Hence, it becomes imperative to understand the aging evolution of the GI system and management of GI disorders in the older population.